26 Dosimetric comparison of 3 TPS in rotational intensity modulated irradiation of breast and regional lymph nodes. (December 2018) - Costa, E.; Bartolucci, L.; Robilliard, M.; Caneva-Losa, S.; Mazal, A.
Abstract : Introduction: Intensity modulated radiotherapy allows to significantly reduce the toxicity to organs at risk (OAR) in radiotherapy of breast cancer while allowing proper coverage of the planning target volumes (PTV). The purpose of this study is to perform a dosimetric comparison of 3 TPS used in our department for the planning of rotational intensity modulated treatment of breast and the following regional nodes: supra and infraclavicular (level IV, III and II nodes) and internal mammary nodes (IMNs). Methods: 10 patients treated for breast cancer and regional nodes (IV, III, II and IMNs) were selected (5 left breasts and 5 right breasts). Prescription doses, delivered in 28 fractions, are 50.4 Gy in the whole breast and the regional nodes, and 63 Gy in the tumor bed (integrated boost). Treatment plans were designed using the 3 following treatment planning systems: Eclipse 13.6 with Photon Optimizer inverse planning algorithm (Varian Medical Systems), RayStation 6.1.1.2 (RaySearch Laboratories AB) and TomoTherapy Planning Station (PS) with VoLO and TomoEdge (Accuray Inc.). Eclipse and RayStation plans were designed using modulated volumetric arc-therapy (VMAT) with 4 partial arcs of 230° amplitude each, while TomoTherapy plans were designed with dynamic jaws, a 5 cm field width and a modulation factor of 3.5. All plans were exported to Artiview (Aquilab) to calculate for each PTV the homogeneity index (HI  = D2-D98/ D50), the CN conformal index (Riet, 1997), the volume covered by isodose 95% of the prescribed dose and the near-maximum dose (D2%). For each plan, the low-dose volume (V5Gy, ) the mean doses to the heart, ipsilateral lung, contralateral lung and breast were recorded. Results: Preliminary results involve 5 patients (3 left breasts and 2 right breasts) and are summarized in Table 1. All treatment plans met acceptable PTV coverage (V95% > 95% for each PTV) as well as OAR medical constraints that are based on our clinical experience. However in the regional nodes and in the breast, even at a certain distance from the tumor bed, some plans for the 3 TPS have D2% greater than 107% of the prescribed dose. Conclusion: This preliminary study shows that the 3 TPS presented here are reliable for the planning of rotational intensity modulated treatment of breast and the regional nodes. Further work will involve the inclusion of a higher number of patients to undertake a more in-depth statistical analysis.